Navigating Leadership in Academia through a Crisis - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2022)
Academic leadership is a fast-paced ever changing entity. When you add an unexpected global pandemic to the mix, it changes academic life beyond anyone's wildest dreams. In this workshop I hope to share how I and my colleagues handled the pandemic and invite the participants to share their experiences. Let's learn from one another!
Keywords: COVID-19; leadership; pandemic; flex-planning; faculty